Salivary biological biomarkers for Alzheimer's disease. (September 2019) - Liang, Dan; Lu, Hao
Highlights: Salivary biomarkers are promising in the diagnosis of Alzheimer's Disease. The current status of potential salivary biomarkers as diagnostic tools in Alzheimer's Disease. Drawbacks of salivary biomarkers in the diagnosis of Alzheimer's Disease. Abstract: Alzheimer's disease (AD) is becoming a threat to aging population all over the world. The pathogenic process of AD is likely initiated many years before clinical onset, thus biomarkers for AD diagnosis are critical for the prevention and therapy for the disease at the early stage in order to reduce the global burden brought by the disease. Saliva is treated as a potential alternative and universal diagnostic fluid that can be collected noninvasively by participants with moderate training and without side effects. Several potential salivary biomarkers, which might prove to be significant diagnostic tools in AD, have been researched. We address here the present and the future of these salivary biological biomarkers for AD.